Calculated phase equilibria for high‐pressure serpentinites and compositionally related rocks close to the MgO–Al2O3–SiO2–H2O (MASH) system. (17th April 2022) - Rebay, Gisella; Powell, Roger; Holland, Tim J. B.
Abstract: The metamorphic evolution of serpentinite has a fundamental bearing on geochemical cycles, mechanical behaviour and seismic properties of the Earth. Phase equilibria in the system MgO–Al2 O3 –SiO2 –H2 O (MASH) provide a 'backbone' for phase equilibria in larger systems that are applicable to serpentinites and also many whiteschists. Phase equilibria for MASH, and departures from MASH, are calculated using the Holland and Powell data set, tc‐ds62, and new activity–composition relations for antigorite and talc. Phase relations are presented using PT projections and compatibility diagrams to highlight the role of P, T and composition on the equilibrium mineral assemblages stable in these chemical systems at high pressure. These phase relations provide the context for pseudosection and other modelling focused on individual rock compositions.